AB0693 Demographic, clinical, laboratory and imaging characteristics of an incidence cohort of 93 patients with large vessel gca. (12th June 2018) - Macchioni, P.; Boiardi, L.; Restuccia, G.; Muratore, F.; Mancuso, P.; Catanoso, M.; Salvarani, C.
Abstract : Background: Few study have evaluated the clinical and imaging data of patients with large vessel GCA (LVGCA) Objectives: To evaluate clinical, demographical and imaging data of an inception cohort of 93 patients with LVGCA recruited in Reggio Emilia (Northern Italy) Methods: All patients with incident large vessel GCA diagnosed between 1 January 2005 and 31 December 2016 and living in the Reggio Emilia area, were identified by capture and re-capture checking of computerised discharge diagnosis codes (ICD10) and using outpatients databases from rheumatology, internal medicine, surgery, pathology, imaging departments of Reggio Emilia Hospital as well as by examining the Reggio Emilia district database for rare diseases. To be included in the study, patients must satisfy the following 2 criteria: Age at disease onset ≥50 years; evidence of large-vessel vasculitis by clinical criteria, angiography, MRA, CTA, PET/CT and/or ultrasonography. Demographic, clinical, laboratory and imaging data collected at first visit were retrived from patients records. Results: There were 93 incident cases of LV GCA (66 women, 71%) during the 12 year study period; Mean ±SD age at diagnosis was 72±9 years. The three most prevalent signs an symptoms were: systemic in 49 pts (52.7%), GCA cranial symptoms in 39 pts (41.9%) and PMR in 35 pts (37.6%). Peripheral ischaemic symptoms were observed only in 8 pts (8.6%). Forty four pts had temporal artery biopsy and 70.5% resulted positive. At US examination the three most common involved arteries were: common carotid artery (59.2% pts), subclavian artery (53.3% pts) and axillary artery (49.3 pts). At PET/CT scan examination the most common involved arteries were: thoracic aorta (72.1% pts), subclavian artery (61.8% pts) and abdominal aorta (58.8% pts). Celiac trunk and mesenteric artery were involved in 18.4% of pts and renal artery in 10.2% of pts. Conclusions: In an inception cohort of LVGCA systemic manifestations had the highest prevalence among presenting symptoms. Imaging studies demonstrated an high prevalence of aortic and subclavian involvement. Disclosure of Interest: None declared